2010
DOI: 10.1063/1.3299268
|View full text |Cite
|
Sign up to set email alerts
|

Binary liquid crystal alignments based on photoalignment in azo dye-doped liquid crystals and their application

Abstract: This work demonstrates the feasibility of binary liquid crystal (LC) alignments, in which two forms of LC alignment are in a single pixel or a specific area using a surface-treated alignment layer and a photoalignment film of the adsorption of azo dyes onto the polymer surface in azo dye-doped liquid crystals. Binary LC alignments that involve two of common LC alignments, which are homogeneous, homeotropic, hybrid, and twisted nematic alignments, are initially demonstrated. Then, a binary LC alignment that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…24 The presented experimental results and our earlier works confirmed that the rate of adsorption of MR dyes onto polymer surface of NOA81 greatly exceeds that onto an indiumtin-oxide (ITO) coated substrate or the surface that is coated with a homogeneous (homeotropic) alignment layer of poly(vinyl alcohol) (PVA) [N,N-dimethyl-N-octadecyl-3aminoprophyltrimethoxy-ailyl chloride (DMOAP)]. 22,23 Therefore, after they are irradiated with a linearly polarized light for a suitable duration, the MR dyes are anisotropically adsorbed only onto the zones of the Fresnel zone plate that are coated with the NOA81 polymer. The fabrication processes and the electrooptical properties of LC Fresnel lenses in DDLCs are elucidated later.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…24 The presented experimental results and our earlier works confirmed that the rate of adsorption of MR dyes onto polymer surface of NOA81 greatly exceeds that onto an indiumtin-oxide (ITO) coated substrate or the surface that is coated with a homogeneous (homeotropic) alignment layer of poly(vinyl alcohol) (PVA) [N,N-dimethyl-N-octadecyl-3aminoprophyltrimethoxy-ailyl chloride (DMOAP)]. 22,23 Therefore, after they are irradiated with a linearly polarized light for a suitable duration, the MR dyes are anisotropically adsorbed only onto the zones of the Fresnel zone plate that are coated with the NOA81 polymer. The fabrication processes and the electrooptical properties of LC Fresnel lenses in DDLCs are elucidated later.…”
Section: Introductionsupporting
confidence: 68%
“…The details could be found in our earlier work. 23 First, the solution of prepolymer (NOA81) in acetone was spin-coated onto an ITOcoated glass substrate that was covered with a homogeneous alignment layer of PVA and rubbed in the direction R. Second, unpolarized UV light with an intensity of ~40 mW/cm 2 was irradiated onto the ITO-coated substrate covered with a homogeneous alignment layer of PVA and a prepolymer layer of NOA81 through a Fresnel-zone-plate mask for 100 sec. Third, the irradiated substrate was immersed in 20:80 of acetone : ethyl alcohol mixture to remove the unpolymerized prepolymer, NOA81.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorbed dyes can be erased and readsorbed by thermal and optical treatments, respectively. The combination of bulk-mediated hybrid photoalignment and homeotropic alignment in a single pixel supports the fabrication of LCDs with a controllable viewing-angle, [52] on which simultaneously displays two images that can be seen from different viewing angles. Other applications in photonic devices, such as optical gratings [53][54][55] and Fresnel lenses have also been investigated [56][57][58][59][60].…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%